Production of micro-porous austenitic stainless steel by powder injection molding - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
The powder space holder (PSH) and powder injection molding (PIM) methods have an industrial competitive advantage that is capable of net-shape production of the micro-sized porous parts. In this study, a micro-porous austenitic stainless steel part was produced by the PSH-PIM process. Spherical poly(methyl methacrylate) (PMMA) particles were used as a space holder material. The effects of fraction and average size of PMMA on properties of sintered micro-porous austenitic stainless steel samples were investigated. It was shown that the fraction and average size of PMMA could be controlled properties. (c) 2007 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: powder injection molding; 316L stainless steel powder; porous metal